Osband’s principle for identification functions - Dimitriadis, Timo; Fissler, Tobias; Ziegel, Johanna (Statistical papers, 2023)
Given a statistical functional of interest such as the mean or median, a (strict) identification function is zero in expectation at (and only at) the true functional value. Identification functions are key objects in forecast validation, statistical estimation and dynamic modelling. For a possibly vector-valued functional of interest, we fully characterise the class of (strict) identification functions subject to mild regularity conditions.